2013
DOI: 10.1007/s10900-013-9720-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Beliefs Regarding Human Papillomavirus Among College Nursing Students at a Minority-Serving Institution

Abstract: Background Cervical cancer is a leading cause of death in U.S. women, with Hispanic women at higher risk of mortality than non-Hispanic white women. While the human papillomavirus (HPV) vaccine represents substantial progress towards cervical cancer prevention, little is currently known about Hispanic student’s beliefs regarding the HPV vaccine. Objective To assess the knowledge, attitudes, behaviors, and beliefs of college students in the U.S.-Mexico border region following the release of the HPV vaccine fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
(26 reference statements)
4
15
0
1
Order By: Relevance
“…Among many factors for intervention programming, attention must be paid to 2 PMT subconstructs: the Perceived Risk and the Response Cost. Perceived risk from no screening was positively associated with intention, consistent with reported studies . On the contrary, perceived response cost (feeling embarrassed, anxiety, and impersonal about screening) was negatively associated with screening intention.…”
Section: Discussionsupporting
confidence: 69%
“…Among many factors for intervention programming, attention must be paid to 2 PMT subconstructs: the Perceived Risk and the Response Cost. Perceived risk from no screening was positively associated with intention, consistent with reported studies . On the contrary, perceived response cost (feeling embarrassed, anxiety, and impersonal about screening) was negatively associated with screening intention.…”
Section: Discussionsupporting
confidence: 69%
“…The results regarding the socio-demographic profile of research subjects confirm the literature on the subject under study. There was a predominance of females, which is in line with other studies that have addressed the same theme (7)(8)(9)(10) . With respect to age, the result of this research corroborates a study in another private university of the state São Paulo, Brazil, that had the same objective (7) .…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, there was a deficit of knowledge related to the characteristics of the human papillomavirus vaccine, including the interval between doses and the vaccination plan, route of administration, contraindications, adverse events and age groups recommended to receive the vaccine in the public health network. These data corroborate the study conducted with nursing students at a university located in the border region of the United States-Mexico, which showed that the level of knowledge among participants was below expectations (8) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The content's validity was evaluated by three experts (nurse, midwife, and epidemiologist), and a feasibility study was previously performed on 15 nurses and five midwives (not publish). The questionnaire was developed in French, based on previous surveys evaluating HPV knowledge, attitudes and perceptions [12][13][14][15][16][17].…”
Section: Study Toolmentioning
confidence: 99%